Description of two new species of nereidids (Annelida: Nereididae) from West Bengal, India, Bay of Bengal - Pradhan, Jyoshna; Villalobos-Guerrero, Tulio F.; Mohapatra, Anil (Zootaxa, 2025)
Two new species of nereidids, Namalycastis solenotognatha sp. nov. and Nereis dhritiae sp. nov. are described in the present paper. These species were collected from two different locations along the intertidal zones, which are situated near mangrove habitats and sandy beaches, respectively. Namalycastis solenotognatha sp. nov. can be distinguished from its resembling congeners from Indian waters mainly by having heterogomph spinigers in supra-preacicular neurochaeta in anterior chaetigers, and lacking notochaetae. Other features related to the size (antennae, eyes, postero-dorsal tentacular cirri, and neuropodial superior lobe) and shape (heterogomph falcigers and spinigers’ blades, and pygidium) of several prostomial and parapodial structures, as well as the number of canals in the jaws, help distinguish the new species. Further, N. dhritiae sp. nov. differs from the three infra group I.B.2 species recorded from India by the presence of a distinct tendon in the blades of notopodial homogomph falcigers, one paragnath on area V, and an anterior row of area VII–VIII with only small paragnaths. Namalycastis solenotognatha sp. nov. and Nereis dhritiae sp. nov. increase the total number of Nereididae species to 73 from the Indian coast, five species belonging to Namalycastis and nine to Nereis.